The Unbearable Modernity of Mobile Money - Ghosh, Ishita; O'Neill, Jacki (Journal of Computer Supported Co-operative Work, 2020)
In this paper, we describe an ethnographic study of a mobile money infrastructure, especially its design, organization, and implementation, and its potential consequences for financial inclusion goals. Through using the analytic lens of infrastructure studies to ground our findings, we observe is that infrastructures emerge in organized practice and use. Moreover, they are constantly evolving with no specific beginning and end; any bounding is contingent on our own methodological and theoretical affiliations as well as our logistical constraints. To this end, we focus our attention on the two different infrastructures – the mobile money and the loan management infrastructures – that were operating in tandem to connect low-income auto-rickshaw drivers to mainstream bank loans. We specifically privilege the human work that goes into making and sustaining this mobile money infrastructure. In doing so, we challenge the ‘unbearable modernity’ of mobile money and its purported effects on helping the poor manage their unpredictable cash flows.